Pengaruh Store Atmosphere dan Kualitas Produk Terhadap Kepuasan Pelanggan pada Eiger Adventure Flagship Store Merr Surabaya: Studi pada Eiger Adventure Flagship Store Merr Surabaya - Laurentina Kurniasari; Ety Dwi Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and analyze the influence of store atmosphere on customer satisfaction at the Eiger Adventure Flagship Store Merr Surabaya. The method used is a quantitative research method which has a positivist philosophy, used in research on certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, quantitative or statistical data analysis aims to test predetermined hypotheses. With the results of this research, there is high customer satisfaction with Eiger Adventure Flagship products at the Merr Surabaya Store for Eiger product users because of the Store Atmosphere and Product Quality which makes consumers feel satisfied with Eiger products. So it is hoped that in the future Eiger will be able to maintain and continue to improve product quality so that consumers do not feel disappointed with Eiger products and also the Eiger store will still be able to maintain and also renew the store atmosphere that has been implemented now because from the results of this research almost all respondents like the atmosphere of the Eiger store. Because with quality products and a pleasant store atmosphere, it will create customer satisfaction with a feeling of satisfaction felt by customers, so customers will become loyal to the Eiger brand.